(untitled) (Itinerarios Educativos, 2019)
The present work is focused on identifying practices and material resources, components of a didactic–pedagogical device (dispositifs), used by teachers to do their job with students, particularly in activities that require certain ways of reading and writing. For this purpose, the case study consists of Geography lessons delivered by a Geography teacher, Ernestina, in the 3rd year (9th grade) of the basic cycle at a state secondary school, in the city of Córdoba, Argentina. The present work aims at providing a contribution to understanding teaching work from a socio–anthropological perspective upon methodological constructions and properties and uses of «ordinary» didactic writing– support artifacts, historically and daily built by teaching collectives. Likewise, this work is intended to be a contribution to studies on didactic–pedagogical devices which enable working with new groups of students coming from socially vulnerable sectors that have been incorporated into secondary school as a result of the advent of compulsory secondary education in Argentina.